2014
DOI: 10.4028/www.scientific.net/jnanor.29.105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing Temperature on the Crystallization of Hematite-Alumina (Fe<sub>2</sub>O<sub>3</sub>-Al<sub>2</sub>O<sub>3</sub>) Nanocomposite and its Influence in EOR Application

Abstract: Usage of magnetic materials is not unusual in oil and gas research, specifically in enhanced oil recovery (EOR) where various magnetic micro-and nanoparticles were used to enhance sweep efficiency, reducing interfacial tension and heat generation. Magnetic nanoparticles which are activated by a magnetic field are anticipated to have the ability to travel far into the oil reservoir and assist in the displacement of the trapped oil. In this work, magnetic Fe2O3-Al2O3 nanocomposite was synthesized and characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Experimental analysis using different NPs performed reasonably in this regard, such as Fe 2 O 3 -Al 2 O 3 [77]. CuO, Fe 2 O 3 , and NiO [81].…”
Section: Influence Of Nanofluids For Em-assisted Eormentioning
confidence: 75%
See 1 more Smart Citation
“…Experimental analysis using different NPs performed reasonably in this regard, such as Fe 2 O 3 -Al 2 O 3 [77]. CuO, Fe 2 O 3 , and NiO [81].…”
Section: Influence Of Nanofluids For Em-assisted Eormentioning
confidence: 75%
“…Despite the significant aspect of employing chemical nanofluids in the reservoir being recently regarded as one of the most reliable processes accredited by modern science and technology, the injected nanofluids in the reservoir usually undergo agglomerations due to the harsh situation of the reservoir and consequently cause the segregation of the fluids from the oil/water interface, as a result of which the nanofluids suffer great trapping in rock pores of the reservoir, and hence the nanofluids transportation will be refrained [49]. Furthermore, the injected chemicals are highly disturbed by high temperature and the high pressure of reservoirs, which leads to some failure, fracture, and degradation of their performance [77]. The EM-assisted nanofluids will be a significant substitute to remedy this critical challenge because the energy disaffected from the EM sources can easily penetrate in the nanofluids, which leads to initiating some disturbances at the oil/water interface, and consequently, the movement of the oil can be facilitated.…”
Section: Influence Of Nanofluids For Em-assisted Eormentioning
confidence: 99%
“…The EOR phenomena of many nanoparticles in a highfrequency external magnetic field has been studied in glassbead packs and sand packs by Yahya et al, including ZnO (Latiff et al, 2011;Zaid et al, 2013;Yahya et al, 2014;Adil et al, 2018), CoFe 2 O 4 (Yahya et al, 2012), Fe 2 O 3 (Yahya et al, 2014), (Soleimani et al, 2014), Al 2 O 3 (Soleimani et al, 2014), and Fe 3 O 4 (Latiff et al, 2016), as shown in Figure 18 (Yahya et al, 2014). However, the impact of temperature on rheology and mobility ratio has been well studied in the past decades.…”
Section: Magnetic Nanoparticle Flooding With Induction Heat Using Hig...mentioning
confidence: 99%
“…Besides, the diffraction peak intensity of ( 110) or (104) in the synthesised samples also decreased with the increase of annealing temperature. The elevated annealing temperature had instigated the growth of hematite nanocrystals with crystallinity enhancement and the reduction of impurities that had formed a superior crystal in the hematite nanostructure film [19,21].…”
Section: Pores On the Nanorod Surfacesmentioning
confidence: 99%